Durable effect of pyrotinib plus capecitabine in HER-2+ breast cancer patient undergoing peritoneal dialysis: A case report and literature review - Jin, Xiangting; Yan, Min; Li, Fanfan (Frontiers in Oncology, 2022)
For patients with end-stage renal disease (ESRD), peritoneal dialysis (PD) and hemodialysis (HD) are important renal replacement treatments. Patients on dialysis usually have a high incidence rate of malignant tumors. In 2020, breast cancer has become the malignant tumor with the highest incidence rate in the world. Human epidermal growth factor receptor-2-positive (HER-2+) breast cancer accounts for 20%-30% of the total breast cancer patients. It is highly invasive and has a poor prognosis. Anti-HER-2 treatment is an important therapy for this type of cancer. There are few case reports of anti-HER2-targeted therapy in dialysis patients. We report a 56-year-old Chinese woman with breast cancer (cT3N1M0, Her-2+/HR-). She underwent peritoneal dialysis for 11 years since she had suffered end-stage renal disease. The clinician prescribed the regimen (pyrotinib 320mg qd + capecitabine 1g bid D1-D14 Q3W). The tumor was significantly reduced after 1 month of single administration of pyrotinib, and partially relieved after 2 months of pyrotinib + capecitabine. The main side effects were grade 2 hand foot syndrome and grade 2 diarrhea. This case shows that the combination of pyrotinib and capecitabine has potential therapeutic benefits in HER-2+ breast cancer patients with end-stage renal disease.